The role of iron in alcohol-mediated hepatocarcinogenesis - Mueller, Sebastian; Rausch, Vanessa (Biological basis of alcohol-induced cancer, 2015)
Alcoholic liver disease (ALD) is the major liver disease in the developed world and characterized by hepatic iron overload in ca. 50 % of all patients. This iron overload is an independent factor of...